STATUS HAK-HAK PRIVAT WARGA NEGARA INDONESIA DI TIMOR LESTE YANG DIPEROLEH BERDASARKAN HUKUM INDONESIA - Wenies Ema Sinaga; I Dewa Gede Palguna (Kertha Negara : Journal Ilmu Hukum, 2015)
The aims of this paper are to study, comprehend, and analyze how state succession has impact to the state obligations to Timor Leste as the state successor in related on the transfer of private rights the Indonesian citizens which have obtained legally under the Indonesia Law the time when Timor Leste (formerly East Timor) was part of to one of the Indonesia provinces. This research of study is to find the law impact when state succession occurs to private individual rights and non-government legal entities shall be treated. Furthermore, the condition existence to give a decent consideration to both Timor Leste and Indonesia government avoiding for its become an international dispute.